Mouse IgA heavy chain gene sequence: implications for evolution of immunoglobulin hinge axons. - Tucker, P W (1981)
The complete nucleotide sequence of the gene and mRNA coding for the constant (C) region of the secreted form of the BALB/c mouse IgA immunoglobulin alpha heavy (H) chain has been determined. As in other immunoglobulins, the three C region domains of the alpha protein, C alpha 1, C alpha 2, and C alpha 3 are coded in separate exons. However, the hinge region of C alpha is not coded on a separate exon as it is in other hinge-containing immunoglobulins. Instead, the alpha hinge is coded as a 5' extension of the C alpha 2 exon, and we suggest that it may have evolved by duplication leading to incorporation of an acceptor RNA splice site into the coding portion of the C alpha 2 exon. Extensions of this concept could provide an explanation for duplications in the human alpha 1 chain.